The longitudinal course of bipolar disorder as revealed through weekly text-messaging: a feasibility study - Bopp, Jedediah M (2010)
OBJECTIVES: To examine the feasibility of collecting course of illness data from patients with bipolar I and II disorder, using weekly text-messaged mood ratings, and to examine the time trajectory of symptom ratings based on this method of self-report. METHODS: A total of 62 patients with bipolar I (n = 47) or II (n = 15) disorder provided mood data in response to weekly cell phone text messages (n = 54) or e-mail prompts (n = 8). Participants provided weekly ratings using the Altman Self-Rating Mania Scale and the Quick Inventory of Depressive Symptoms–Self Report. Patients with bipolar I and II disorder, and men and women, were compared on percentages of time in depressive or manic mood states over up to two years. RESULTS: Participants provided weekly ratings over an average of 36 (range 1–92) weeks. Compliance with the procedure was 75%. Overall, participants reported depressive symptoms 47.7% of the time compared to 7% of entries reflecting manic symptoms, 8.8% reflecting both depressive and manic symptoms, and 36.5% reflecting euthymic mood. Participants with bipolar I disorder reported more days of depression and were less likely to improve with time than participants with bipolar II disorder. Gender differences observed at the beginning of the study were not observed at follow-up. CONCLUSIONS: The results are similar to those of other longitudinal studies of bipolar disorder that use traditional retrospective, clinician-gathered mood data. Text-message based symptom monitoring during routine follow-up may be a reliable alternative to in-person interviews.